Selection Platform Music Service Cloud with Simple Multi-Attribute Rating Technique – User Service Application (SMART ALP) - Rizki Bagaswara Putra; Setiawan, Bambang (Journal of Applied Science, Engineering, Technology, and Education, 2022)
SMART is a popular Multi-Criteria Decision Making (MCDM) method that helps make accurate decisions to solve problems and choose the best decision using a linear additive model to generate values ​​for various alternatives. The SMART ALP used in this study is a development of the SMART method by providing three additional dimensions, application, service, and user, to emphasize the correlation with the corridors of the cloud music service platform. The object of research: (1) Apple Music, (2) Deezer, (3) iHeartRadio, (4) JOOX, (5) Melon, (6) NetEase Cloud Music, (7) Qobuz, (8) SoundCloud, (9) Spotify, (10) Tidal, (11) TuneIn, and (12) YouTube Music. Convenience criteria and playlist management with 60.4% (29 of 48 respondents) and 58.3% (28 of 48 respondents) responses, respectively. Performance criteria and simplicity with 66.7% (32 of 48 respondents) and 68.8% (33 of 48 respondents) responses, respectively. Music quality criteria with an answer of 93.8% (45 out of 48 respondents). The study results show that Spotify, YouTube Music, Joox, Apple Music, and SoundCloud are the five best cloud music service platforms with a total score of 8422 points, respectively, YouTube Music 6483 points, and Joox 3824 points, Apple Music 2039 points, and SoundCloud 1275. Points.